Pinellic Acid Isolated from Quercetin-rich Onions has a Peroxisome Proliferator-Activated Receptor-Alpha/Gamma (PPAR-α/γ) Transactivation Activity - Doi, Mikio; Morita, Naoki; Okuzawa, Tsugumi; Ohgiya, Satoru; Okamoto, Daisaku; Sato, Kenichi; Ito, Yukiya; Matsuura, Hideyuki; Hashidoko, Yasuyuki (Planta Medica, 2022)
Quercetin, a flavonol, is a functional compound that is abundant in onions and is known to have antioxidant and anti-inflammatory effects. Quercetin and its glucoside are known to function as peroxisome proliferator-activated receptor (PPAR) ligands and showed high PPAR-α transactivation activity but little PPAR-γ transactivation activity in some reports. In this study, we demonstrated that an aqueous extract of a quercetin-rich onion cultivar increased transactivation activities not only of PPAR-α but also of PPAR-γ. We isolated (9S,12S,13S)-(10E)-9,12,13-trihydroxyoctadec-10-enoic acid (pinellic acid) obtained from the aqueous extract using PPAR-γ transactivation as an index. Furthermore, it was revealed that pinellic acid could transactivate PPAR-α. Our findings are the first report mentioned showing that trihydroxyoctadec-10-enoic acids showed PPAR-α/γ transactivation activities.
Keywords: Allium cepa; Amaryllidaceae; (9S,12S,13S)-(10E)-9,12,13-Trihydroxyoctadec-10-enoic acid (Pinellic acid); (S) configuration; peroxisome proliferator-activated receptor; nuclear factor-κB